Faces Amid the Mountains: A Barthesian Reading of a Photograph in Sore - Aninditya Ardhana Riswari; Febrian Putra; Novia Sisca Handayani; I Putu Adi Putra Wiwana (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
In an era characterized by media saturation, cinematic visuals possess considerable ideological and emotional significance. This study analyzes the portrait of a Ladakhi woman in Sore (2025), directed by Yandy Laurens, to investigate how visual elements in mainstream cinema serve as cultural representations and evoke emotional responses. Employing Roland Barthes's semiotic notions of studium and punctum, the photograph is examined as a locus of dual significance: intellectually comprehensible via cultural norms and emotionally resonant through subtle, unarticulated nuances. Utilizing a qualitative descriptive methodology, the analysis focuses on Barthes’s semiotic framework as delineated in Camera Lucida (1980). Each visual component encompasses gesture, attire, look, color, and background, which are analyzed for their representational and emotional meaning. The theoretical foundation is grounded in Barthes's multiple semiotic layers and Stuart Hall's encoding/decoding paradigm, which emphasize that meaning is not fixed but is influenced by viewers through cultural and emotional settings. The findings underscore how studium elucidates the socio-cultural backdrop of Ladakh, gendered identity, and physical isolation, whereas punctum manifests in nuanced visual features, particularly the woman's partially obscured mouth, which elicit profound, personal responses. These characteristics show that the photograph is not just a decorative narrative, but also a place for international empathy and societal commentary. This research illustrates that visual components in movies can convey intricate cultural tales and emotional depth. Barthes posits that cinematic images function as affective texts that connect aesthetics and ethics, documentation and emotion, so cultivating critical awareness and empathic engagement with oppressed identities.